Results of contralateral anastomosis of microvascular free flaps in head and neck reconstruction - Gschoßmann, Juliane; Balk, Matthias; Rupp, Robin; Müller-Hübner, Sarina Katrin Ursel; Allner, Moritz; Sievert, Matti; Mantsopoulos, Konstantinos; Koch, Michael; Iro, Heinrich; Gostian, Antoniu-Oreste (Ent-Ear Nose & Throat Journal, 2022)
Objectives: Despite various solutions to the issue of ipsilateral vessel-depleted neck in microvascular head and neck reconstruction, concrete data on its safety and implementation are scarce. This paper focuses on the feasibility and success rates of contralateral anastomosis in free flap reconstruction in the head and neck region. Methods: This single-center retrospective study at a tertiary referral center includes all patients who underwent free flap reconstruction of the head and neck with contralateral anastomosis between January 1st, 2007 and February 28th, 2021. Primary objectives were frequency, success, and flap-associated complication rates. Secondary objectives were recipient vessels and flap type. Results: Of 318 patients who underwent microvascular reconstruction, anastomosis was performed on the contralateral side of the neck in 32 patients (10.0%). Recipient vessels involved mainly the superior thyroid artery (74.2%; n = 23) and the facial vein (51.1%; n = 23). Thirty patients (93.8%) received a radial forearm free flap. Flap-associated complications occurred in 12.5% of included cases (n = 4): one partial flap necrosis (3.1%), one anastomotic insufficiency (3.1%), one venous thrombosis of the microvascular pedicle (3.1%), and one wound dehiscence (3.1%). All of these complications were resolved without complete flap loss. Conclusion: This study demonstrates that contralateral anastomosis is a successful and safe option in microvascular head and neck reconstruction, especially using a radial forearm free flap. Thus, anastomosing to the contralateral side of the neck can be advocated as a valuable option in the ipsilateral vessel-depleted neck.
CRIS-Team Scopus Importer:2022-07-15
Keywords: contralateral anastomosis; free flaps; head and neck cancer; microvascular reconstruction; recipient vessels; vessel-depleted neck